If it's not what You are looking for type in the equation solver your own equation and let us solve it.
42=7(z+5)
We move all terms to the left:
42-(7(z+5))=0
We calculate terms in parentheses: -(7(z+5)), so:We get rid of parentheses
7(z+5)
We multiply parentheses
7z+35
Back to the equation:
-(7z+35)
-7z-35+42=0
We add all the numbers together, and all the variables
-7z+7=0
We move all terms containing z to the left, all other terms to the right
-7z=-7
z=-7/-7
z=1
| 2(3x-5)+1=(-4+5)+(7x-8) | | 3x+40=73 | | F=1500(1.074)t | | 5x-300=5 | | -x+10=-2x+2 | | 4y+16=-32 | | 15+y3=6 | | 7p-16=82 | | 9h-20=19h | | 3a^2-18=0 | | 2(3x-60)=84 | | x2−6x=27 | | −1−7x+42=36−6x | | X^2+30=-9x | | 8+18m=20m | | −6+8x−8=4+2x | | -3h^2=-108 | | 5x/3+10=50 | | 2(3.5n+6)=2.5n-2) | | -6a=-59 | | x^2-4=-2x+80 | | -5x+1=7x+25 | | g-18=32 | | −18−6k=6+18k | | -6z+6=-5z | | V=-8+5v | | 5n+34=−2+14n | | 3x/2+x/3=11 | | x+81/3=123/4 | | b-36=4 | | 3x=1+8x | | 0.06x0.6=0.036 |